The identification and functional characterization of substrates of the C. elegans caspase CED-3 - Taylor, Rebecca C. (Trinity College (Dublin, Ireland). Department of Genetics, 2007)
The founding member of the caspase family of proteases is the C. elegans caspase, CED-3. CED-3 is the only caspase required for programmed cell deaths in the worm, but we know very little about how this protease coordinates the complex and reproducible downstream events of cell death. In this study, we aimed to gain a better understanding of how CED-3 controls the execution of programmed cell death by identifying its cellular substrates through proteomic analysis. It was anticipated that a better understanding of the role of CED-3 in worm programmed cell death (PCD) would also generate insights into the coordination of PCD by the mammalian counterparts of this enzyme.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin